Influence of environmental winds on propagation and motion of thunderstorms in northern Greece - Sioutas, M.V.a d; Flocas, H.A.b c (Journal of Geophysical Research D: Atmospheres, 1996)
The prediction of propagation and motion of thunderstorm activity, especially when heavy rainfall accumulation amounts could occur, is a matter of great importance. The objective of this study is to examine the possibility of using the environmental wind data for the problem of assessing predictability of the propagation and movement of thunderstorms in northern Greece. The propagation of radar thunderstorm echoes (radar echo reflectivity maxima) and cell movement (fine radar echo patterns) were determined for the spring and summer thunderstorms in 1992 and 1993 (April to September). Radar data were used by examining and analyzing digitally recorded plan position indicator for the entire time that the radar was operated. Multicell and single-cell thunderstorms were identified and thunderstorm propagation and cell motion were calculated for each. Environmental winds at standard levels of 850, 700, and 500 hPa were considered and, additionally, a mean 0- to 6-km layer density-weighted wind was also examined. In northern Greece, winds and radar thunderstorm echoes rarely moved from the clockwise sector 070° to 220° (ENE - SW). The movement of thunderstorm cells was not only steered by the 700-hPa level wind but was also well represented by the wind at the 500-hPa level and by the average wind in the layer 0-6 km. Using standard levels, cell motion can be determined by adding 5° to 500-hPa wind direction and reducing the 500-hPa wind speed by 30%. With the use of the mean 0- to 6-km density-weighted wind, cell motion can be represented by adding 5° to the 0- to 6-km wind direction and increasing 35% the 0- to 6-km wind speed. The propagation of multicell and single-cell thunderstorm echoes was very similar, in spite of initial expectations, and was approximately equal to the cell motion, suggesting that the new cells grew on all sides of existing multicell thunderstorms. The majority of northern Greece thunderstorms do not propagate significantly and their motion is substantially translational and similar to cell motion. However, in cases of severe thunderstorms, propagation was indicated. Characteristic cases of storm propagation are presented and vertical wind shear is investigated as a particularly important factor in influencing storm structure and evolution and the resulting storm propagation.
cited By (since 1996)3
Keywords: cell motion; Greece; storm propagation; thunderstorm; wind; wind data